Kajian Hukum Asuransi Dalam Perspektif Hukum Bisnis di Indonesia - Kevin Aurel Hendra; Nathasya Calista; Zaskia Fadhillah; Najwa Fadilah Affandi; Wahyu Firmansyah; Helfira Citra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This study examines the concept and application of insurance within the framework of business law, with particular emphasis on legal regulation, fundamental insurance principles, and dispute resolution in insurance claims. The research employs a normative juridical method through statutory and literature approaches, analyzing relevant laws, regulations, and legal doctrines related to insurance practices. The findings indicate that insurance plays a crucial role in providing legal protection and financial security by transferring risk from the insured to the insurer. However, in practice, disputes frequently arise due to differences in the interpretation of policy provisions and the application of the principle of indemnity. These issues highlight the importance of legal clarity, transparency, and good faith in insurance agreements. Therefore, a comprehensive understanding of insurance principles and contractual obligations is essential to ensure legal certainty and fairness for both insurers and policyholders.